Manajemen Birokrasi Profesional Dalam Meningkatkan Pelayanan Publik - Jaelan Usman (Otoritas : Jurnal Ilmu Pemerintahan, 2011)
Professional management of public services should be more goal-oriented paradigm of governance that is based on a new management approach, both theoretically and practically. Simultaneously, a paradigm of governance goal is expected to eliminate practices that Weberian bureaucracy is negative as hierarkhikal bureaucratic structures that result in operating cost is more expensive (high cost economy) than the benefits gained, the prevalence of red tape, lack of initiative and creativity of the apparatus, the growth of culture mediokratis (as opposed to meritocratic culture) and in-efficiency. Therefore, institutions of public service can be done by government and non-governmental organizations. If the government, the organization of government bureaucracy is the forefront of the organization (street level bureaucracy) related to public service. If the non-government, then shaped the organization of political parties, religious organizations, nongovernmental organizations and civil society organizations to another. Anyone pelayanananya institutional forms, the most important thing is how to provide assistance and facilities to the community in order to meet the needs and interests.Manajemen profesional pelayanan publik harus lebih berorientasi pada tujuan paradigma pemerintahan yang didasarkan pada pendekatan manajemen baru, baik secara teori maupun praktis. Secara bersamaan, paradigma dari tujuan pemerintahan diharapkan dapat menghilangkan praktek bahwa birokrasi Weberian adalah negatif seperti struktur birokrasi hierarkhikal yang menghasilkan biaya operasional lebih mahal (ekonomi biaya tinggi) daripada manfaat yang diperoleh, prevalensi birokrasi, kurangnya inisiatif dan kreativitas aparatur, pertumbuhan mediokratis budaya (sebagai lawan dari budaya meritokratis) dan in-efisiensi. Oleh karena itu, institusi pelayanan publik dapat dilakukan oleh pemerintah dan organisasi non-pemerintah. Jika pemerintah, organisasi birokrasi pemerintah adalah garis depan organisasi (jalan birokrasi tingkat) terkait dengan pelayanan publik. Jika non-pemerintah, kemudian membentuk organisasi partai politik, organisasi keagamaan, lembaga swadaya masyarakat dan organisasi masyarakat sipil yang lain. Siapapun pelayanananya bentuk kelembagaan, hal yang paling penting adalah bagaimana memberikan bantuan dan kemudahan kepada masyarakat dalam rangka memenuhi kebutuhan dan kepentingan.